The feeding of Cod (Gadus morhua) on Flemish Cap, 1989-90 - Paz, Xabier; Casas-Sánchez, José Miguel; Pérez-Gándaras, Germán (1993)
The food and feeding of Flemish Cap cod (Gadus morhua) in summer are described for 2 years, 1989 and 1990. The summer feeding intensity was high and the prey spectrum was narrow in both years. Hyperidea and redfish stood out in the diet of the Flemish Cap cod. Illex illecebrosus and polychaetes had a high annual variability. In the juvenile cod diet, invertebrates (crustaceans and polychaetes) were dominant and in the adults the most important prey were fish, mainly redfish. The Schoener overlap index was calculated to study the intraspecific diet overlap. It was noted that cod diet changed between age groups 3-5 and 6-10. Cannibalism rates showed year-to-year fluctuations. Ingestion of redfish was similar in both years and a direct relationship between cod length and the length of redfish they preyed on was noted.